2016
DOI: 10.1016/j.minpro.2016.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Depressing effect of fine hydrophilic particles on magnesite reverse flotation

Abstract: The influence of fine particles on the flotation separation of minerals is becoming increasingly important as new, fine grained deposits are exploited. Fine particles float poorly and less selectively under normal flotation conditions, having detrimental effects on recovery of other minerals. The reasons of this interacting effect are complex, which may be entrainment, pH variation, dissolved ions from mineral surfaces, aggregation/dispersion and coating behavior of particles or even the competitive adsorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(42 citation statements)
references
References 59 publications
2
37
0
3
Order By: Relevance
“…Figure 8 shows the zeta potential of quartz as a function of pH in the absence and presence of calcium ions. The IEP of quartz in distilled water was observed around pH = 2, which was in good agreement with results reported by other researchers [33][34][35]. It can be seen that the IEP values did not change with the increase of calcium ion concentration, but the quartz surface was less negatively charged in the presence of Ca 2+ above pH 3.4.…”
Section: Zeta Potentials Of Pure Minerals In the Presence Of Calcium supporting
confidence: 91%
“…Figure 8 shows the zeta potential of quartz as a function of pH in the absence and presence of calcium ions. The IEP of quartz in distilled water was observed around pH = 2, which was in good agreement with results reported by other researchers [33][34][35]. It can be seen that the IEP values did not change with the increase of calcium ion concentration, but the quartz surface was less negatively charged in the presence of Ca 2+ above pH 3.4.…”
Section: Zeta Potentials Of Pure Minerals In the Presence Of Calcium supporting
confidence: 91%
“…ZP measurements have revealed that cationic and anionic collectors have pronounced effects on the surface charge of Mg carbonate minerals (Table 2). It has been observed that cationic collector dodecylamine (DDA) shifts the IEP of Mg carbonates to basic pH 9, and exhibits negative ZP up to pH 12 [23]. On the other hand, with anionic collector sodium oleate (NaOl), Mg carbonates experience negative ZP from pH 3 to 11 [34]; it can also be noted that the ZP of Mg carbonates become negative with increased NaOl concentration [31].…”
Section: Electrical Chargementioning
confidence: 99%
“…Magnesite (MgCO 3 ) is the main source of magnesium oxide mineral, and is used in metallurgy, construction, the chemical industry, and other fields [1,2]. As the market demand for magnesium oxide mineral is increasing, the amount of high quality magnesite is gradually decreasing.…”
Section: Introductionmentioning
confidence: 99%